Infection probability score : a predictor of clostridium difficile-associated disease onset in patients with haematological malignancy - Apostolopoulou, Eleni A.; Terzis, Konstantinos; Elefsiniotis, Ioannis S.; Raftopoulos, Vasilios (My University, 2011)
Purpose: to assess the predictive power of three systems: Infection Probability Score, APACHE II and KARNOFSKY score for the onset of Clostridium difficile-associated disease (CDAD) in hematology-oncology patients. Methods and sample: A retrospective pilot surveillance survey was conducted in the hematology unit of a general hospital in Greece. Data were collected by using an anonymous standardised case-record form. The sample consisted of 102 hospitalized patients. Results: The majority of the patients (33.3%) suffered from acute myeloid leukemia. The cumulative incidence of CDAD was 10.8% and the incidence rate of C difficile associated diarrhea was 5 per 1000 patient-days (14.2 per 1000 patient-days at risk). Patients with CDAD had twofold higher time of mean length of hospital stay compared with patients without CDAD (38.82 ± 23.88 vs 19.45 ± 14.56 days). Additionally patients with CDAD had received a greater number of different antibiotics compared to those without CDAD (5.18 ± 1.99 vs 2.54 ± 2.13), suffered from diabetes, from non Hodgkin's lymphoma, had a statistically significant higher duration of neutropenia ≥3 days and had received antifungal treatment. The best cutoff value of IPS for the prediction of CDAD was 13 with a sensitivity of 45.5% and a specificity of 82.4%. Conclusions: IPS is an early diagnostic test for CDAD detection.
Keywords: APACHE II; Clostridium difficile-associated disease; Healthcare-associated infections; Hematology; Infection probability score; KARNOFSKY